Pembelajaran Fisika Dengan Metode Mindmapping Menggunakan Mindmeister Pada Materi Rangkaian Arus Searah - Dewantara, Dewi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
This article aims to describe the improvement of student learning outcomes in direct current circuit material after applying learning with mind mapping methods using the mindmeister application. The type of this research is pre-experiment with one group pretest posttest design method. The number of research samples was 15 students. The data collection technique used was the pre-test and post-test. Data were analyzed using the N-Gain test and paired t-test. The N-gain results obtained a value of 0.59 which means that the increase is in the medium category. The results of the t-test analysis obtained the value t = -6,650 with sig (2-tailed) = 0,000 which is smaller than the significance level of 0.05. The conclusion from the results of this study is that there is an increase in student learning outcomes in direct current circuit material after applying Learning with the mind mapping method using mindmeister.